The health promoting sports club model: An intervention planning framework. (30th September 2020) - Van Hoye, A; Johnson, S; Geidne, S; Donaldson, A; Rostan, F; Lemonnier, F; Vuillemin, A
Abstract: Background: Researchers and policymakers have acknowledged sports clubs (SCs) as health promoting settings. Limited research links the health promoting sports club (HPSC) concept with evidence-driven strategies to offer SCs guidance to develop health promotion interventions. As implementation science insists on theoretically grounded interventions, this work's objective was to provide SCs an evidence-driven intervention framework for planning health promotions. Methods: A 4-step process was undertaken: 1) investigate indicators for SCs to be considered health promoting, 2) adapt the theoretical HPSC concept to create a HPSC model, 3) reformulate published evidence-driven guidelines into implementable intervention components (ICs) and 4) merge the model with the ICs to provide an intervention planning framework for SCs. During 3 workshops, researchers defined the model elements and ICs. Workshop participants classified ICs into the HSPC model. Each IC could be classified multiple times within the model. Results: Researchers drafted 5 HPSC indicators: 1) an approach embracing all SC actions, 2) involve all SC levels in actions and decisions, 3) involve external partners, 4) promoting health is continuous and iterative and 5) base actions on needs. To create the HPSC model, elements were defined: 3 SC levels (club, management, coaches) and 4 health determinants (organizational, social, environmental, economic) per level based on the indicators. Published guidelines from literature reviews aided in developing 14 strategies with 55 ICs. Workshop classification of ICs into the model included: club (n = 79), management (n = 67) and coaches (n = 48). Conclusions: The theoretical HPSC model and intervention planning framework act as starting points to develop and implement interventions to increase HP efforts by stakeholders in several ways: 1) SCs can apply strategies based on goals, 2) SCs can target specific levels with corresponding ICs or 3) ICs can target specific health determinants. Key messages: A Health Promoting Sports Club model defines 4 health determinants at 3 levels (coach, management operational) of sports clubs to plan, develop and implement targeted health promotion activities. This HPSC intervention planning framework has 14 strategies with 55 intervention components targeting multiple sports club levels giving stakeholders a path to become a health promoting sports club.